2019
DOI: 10.3390/cells8050398
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Pathway in Mammalian Adaptive Immune System

Abstract: The Hippo pathway was originally identified as an evolutionarily-conserved signaling mechanism that contributes to the control of organ size. It was then rapidly expanded as a key pathway in the regulation of tissue development, regeneration, and cancer pathogenesis. The increasing amount of evidence in recent years has also connected this pathway to the regulation of innate and adaptive immune responses. Notably, the Hippo pathway has been revealed to play a pivotal role in adaptive immune cell lineages, as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 124 publications
1
43
0
Order By: Relevance
“…A recent study has shown that in Drosophila the Hippo signaling pathway regulates innate immune response and is activated downstream of the Toll like receptor (TLR) pathway to regulate production of anti-microbial peptides ( 21 ). Emerging evidence has indicated that YAP is also implicated in the regulation of macrophage immune responses ( 46 ). Zhou et al show that depletion of YAP in macrophages relieves pro-inflammatory responses in inflammatory bowel disease (IBD) via enhancing macrophage M2 polarization and suppressing IL6 production ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that in Drosophila the Hippo signaling pathway regulates innate immune response and is activated downstream of the Toll like receptor (TLR) pathway to regulate production of anti-microbial peptides ( 21 ). Emerging evidence has indicated that YAP is also implicated in the regulation of macrophage immune responses ( 46 ). Zhou et al show that depletion of YAP in macrophages relieves pro-inflammatory responses in inflammatory bowel disease (IBD) via enhancing macrophage M2 polarization and suppressing IL6 production ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although EGFR acquires drug resistance to TKI via the T790M mutation, TEAD inhibition effectively reduces the viability of TKI-resistant lung adenocarcinoma cells [166,167]. TEAD also contributes to the immune escape of NSCLC cells by directly transcribing PD-L1 , which, in turn, causes CD8 + T cell exhaustion [43,168]. Furthermore, TEAD increases EGFR expression by directly binding to the EGFR promotor, which induces tumorigenesis and drug resistance in esophageal cancer [39].…”
Section: Teads As Mediators Of Cancer Genesmentioning
confidence: 99%
“…48,49) In contrast, aberrant activation of the Hippo pathway impairs tissue development, stem cell maintenance, and differentiation. 50) In addition to those cell-autonomous functions, recent studies revealed that the Hippo pathway also mediates non-cell autonomous functions, such as cell competition [51][52][53][54][55] and immune responses, [56][57][58][59][60] which play a pivotal role in the homeostatic control of multicellular organisms. 61,62) Thus, collectively, the Hippo intracellular signaling pathway acts as a nexus and integrator for multiple signals from the cellular microenvironment, regulat-ing multiple aspects of cell biology, and thereby contributing to cell-fate determination 63) (Fig.…”
Section: Introductionmentioning
confidence: 99%